2017
DOI: 10.1016/j.watres.2017.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of DNA viruses in effluents of membrane bioreactors in Traverse City, MI (USA) and La Grande Motte (France)

Abstract: This study assesses diversity of DNA viruses in the effluents of two membrane bioreactor (MBR) wastewater treatment plants (WWTPs): an MBR in the United States and an MBR in France. Viral diversity of these effluents is compared to that of a conventional activated sludge WWTP in the U.S. Diversity analysis indicates Herpesvirales to be the most abundant order of potentially pathogenic human DNA viruses in wastewater treated effluent in all utilities. Other potentially pathogenic human viruses detected include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…The 2013 study also indicates that bacteriophages can still be detected after hypochlorite treatment in the East Lansing wastewater treatment plant (41), though their hosts are retained or destroyed in the treatment facility. Phages have been used as indicators for the presence of pathogenic bacteria and viruses in untreated or treated sewage (46), as well as surface water and groundwater (47).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The 2013 study also indicates that bacteriophages can still be detected after hypochlorite treatment in the East Lansing wastewater treatment plant (41), though their hosts are retained or destroyed in the treatment facility. Phages have been used as indicators for the presence of pathogenic bacteria and viruses in untreated or treated sewage (46), as well as surface water and groundwater (47).…”
Section: Discussionmentioning
confidence: 96%
“…In 2013, a metagenomic study of phages in wastewater influent and effluent was conducted using water from an East Lansing, MI, treatment plant (41). While the hosts of these phages could not be determined, that study indicated that most phages were tailed, with the long, non-contractile-tailed phages of the family Siphoviridae representing ϳ43% of the total phage population.…”
Section: Discussionmentioning
confidence: 99%
“…These may include human pathogens such as those introduced by fecal matter, but, more importantly, bacteriophage which serve to regulate bacterial populations (O'Brien et al, 2017). Bacteriophage alter biogeochemical cycles through lysis of bacterial cells (Díaz-Muñoz and Koskella and Brockhurst, 2014) and impact eukaryotes that depend on bacterial populations, thus having a significant impact on the greater ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Each aquarium system is a unique ecosystem that is closed and controllable but mimics native aquatic habitats. Although previous studies have proved the feasibility of metagenomic approaches for exploring viromes in natural aquatic environments (Roux et al, 2012; Williamson et al, 2012; Hurwitz and Sullivan, 2013; Tseng et al, 2013; Brum et al, 2015; Kim et al, 2015, 2016), to the best of our knowledge, no studies have been published to date on viromes in an aquarium ecosystem, which is an engineered system but not wastewater (Cantalupo et al, 2011; Tamaki et al, 2012; Aw et al, 2014; O’Brien et al, 2017) or host-associated system (Minot et al, 2011; Ross et al, 2013; Lim et al, 2015). Thus, in a collaborative effort as part of Aquarium Microbiome Project 1 , we explored the relationship of viromes with exhibit environments, physiochemical parameters, and resident animals.…”
Section: Introductionmentioning
confidence: 99%